Effective elastic thickness of South America and its implications for intracontinental deformation - Perez-Gussinye, M; Lowry, A; Watts, A (2007)
The flexural rigidity or effective elastic thickness of the lithosphere, Te, primarily depends on its thermal gradient and composition. Consequently, maps of the lateral variability of Te in continents reflect their lithospheric structure. We present here a new Te map of South America generated using a compilation of satellite-derived (GRACE and CHAMP missions) and terrestrial gravity data (including EGM96 and SAGP), and a multitaper Bouguer coherence technique. Our Te maps correlate remarkably well with other proxies for lithospheric structure: areas with high Te have, in general, high lithospheric mantle shear wave velocity and low heat flow and vice versa. In this paper we focus on the Te of the stable platform. We find that old cratonic nuclei (mainly Archean and Early/Middle Proterozoic) have, in general, high Te (>70 km), while the younger Patagonian Phanerozoic terrane has much lower Te (20-30 km), suggesting that Te is related to terrane age as has already been noted in Europe. Within cratonic South America, Te variations are observed at regional scale: relatively lower Te occurs at sites that have been repeatedly reactivated throughout geological history as major sutures, rift zones, and sites of hot spot magmatism. Today, these low Te areas are surrounded by large cratonic nuclei. They concentrate most of the intracontinental seismicity and exhibit relatively high surface heat flow and low seismic velocity at 100 km depth. This implies that intracontinental deformation focuses within relatively thin, hot, and hence weak lithosphere, that cratonic interiors are strong enough to inhibit tectonism, and that the differences in lithospheric rigidity, structure, and composition between stable cratons and sites of intracontinental deformation are not transient, and may have been maintained, in some cases, for at least 500 m.y. Copyright 2007 by the American Geophysical Union.